Implementation of Market Day in Developing Social Emotional of 4-5 Years Old Children at Pagaruyung Kindergarten - Saumi, Wulan Nisfu; Utama, Ferdian; Dea, Leli Fertiliana; Yusuf, Muhammad; Jannah, Siti Roudhatul (CV. Creative Tugu Pena, 2024)
This research is motivated by its benefits Market Day to develop soft skill For example, children are brave, creative, have entrepreneurial skills, are responsible, don't give up easily, are independent, conscientious, capable and have social skills. Implementation Market Day This is very educational, namely that children will directly interact with the surrounding environment such as peers and educators. This research aims to determine implementation Market Day in developing the social and emotional development of children aged 4-5 years at Pagaruyung Kindergarten. This research is qualitative research using descriptive methods with the aim of maximizing implementation Market Day to develop the social and emotional development of children aged 4-5 years at Pagaruyung Kindergarten. Research methods include observations and interviews. This research aims to determine implementation Market Day in developing the social and emotional development of children aged 4-5 years at Pagaruyung Kindergarten. The results of this research show that in implementation Market Day social emotional children aged 4-5 years have met the indicators of achieving social emotional abilities in accordance with the social emotional development achievements of children aged 4-5 years. Research contributions as additional materials, guidelines, references and information as well as the results of this research can provide insight regarding implementation Market Day in developing social emotional children aged 4-5 years.